Penerapan Model Attention, Interest, Desire, Action (AIDA) pada Promosi Produk Hmns di Media Sosial Instagram - Azhar, Abdurrafi; Erlangga, Christopher Yudha (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
Product promotion via social media, especially Instagram, has become an effective strategy in reaching consumers widely and increasing audience engagement. This research aims to analyze the application of the AIDA (Attention, Interest, Desire, Action) model in the promotion of the perfume product "Untitled Humans Aroma 02" by HMNS via Instagram. The campaign attracts attention with a striking visual design, generates interest through collaboration with Maliq & D’Essentials, creates desire with an exclusive approach, and drives action through an interactive call to choose a product launch date. This research uses a qualitative descriptive method with a content analysis approach. Data was obtained from direct observation of promotional campaigns uploaded to the official HMNS Instagram account. Analysis was carried out based on the AIDA model to evaluate the effectiveness of each promotional stage in creating audience engagement and encouraging purchasing decisions. The research results show that promotions via Instagram are successful in attracting attention through aesthetic visuals and relevant messages. The strategic collaboration with Maliq & D'Essentials succeeded in increasing audience interest, especially music fans. Consumer desires are strengthened by the concept of product launches that involve the audience through voting, creating a sense of participation. Additionally, a clear, direct call to action encourages the audience to take immediate action. The conclusion of this research is that the application of the AIDA model to promotions on Instagram has proven effective in increasing engagement and encouraging purchasing decisions. Promotional strategies that combine interactivity, attractive visuals and an emotional approach can be used as a reference for other brands in designing marketing campaigns on social media